Two novel polymorphic forms of iron‐chelating agent deferiprone. Issue 2 (31st January 2020) - Rajendrakumar, Satyasree; Durga, Anuja Surampudi Venkata Sai; Nanubolu, Jagadeesh Babu; Balasubramanian, Sridhar
Abstract : Two novel polymorphic forms of deferiprone were detected during crystallization experiments. In the crystal packing of one polymorph, the deferiprone molecules were aggregated as corrugated sheets, as in the original structure, whereas, in the other novel polymorph, the molecules were aggregated as a square‐grid network. Abstract : Thalassemia is a genetic blood disorder requiring life‐long blood transfusions. This process often results in iron overload and can be treated by an iron‐chelating agent, like deferiprone (3‐hydroxy‐1, 2‐dimethylpyridin‐4‐one), C7 H9 NO2, in an oral formulation. The first crystal structure of deferiprone, (Ia), was reported in 1988 [Nelson et al. (1988). Can. J. Chem. 66, 123–131]. In the present study, two novel polymorphic forms, (Ib) and (Ic), of deferiprone were identified concomitantly with polymorph (Ia) during the crystallization experiments. Polymorph (Ia) was redetermined at low temperature for comparison of the structural features and lattice energy values with polymorphs (Ib) and (Ic). Polymorph (Ia) crystallized in the orthorhombic space group Pbca, whereas both polymorphs (Ib) and (Ic) crystallized in the monoclinic space group P 21 / c . The asymmetric units of (Ia) and (Ib) contain one deferiprone molecule, while polymorph (Ic) has three crystallographically independent molecules ( A, B and C ). All three polymorphs have similar hydrogen‐bonding features, such as an R 2 2 (10) dimer formed by O—H…O hydrogen bonds, an R 4 3 (20) tetramer formed by C—H…O hydrogen bonds and π–π interactions, but the polymorphs differ in their molecular arrangements in the solid state and are classified as packing polymorphs. O—H…O and C—H…O hydrogen bonds lead to the formation of two‐dimensional hydrogen‐bonded parallel sheets which are interlinked by π–π stacking interactions. In the three‐dimensional crystal packing, the deferiprone molecules were aggregated as corrugated sheets in polymorphs (Ia) and (Ic), whereas in polymorph (Ib), they were aggregated as a square‐grid network. The characteristic crystalline peaks of polymorphs (Ia), (Ib) and (Ic) were established through powder X‐ray diffraction analysis. The Rietveld analysis was also performed to estimate the contribution of the polymorphs to the bulk material.